More jobs: better cities - a framework for city action on jobs. - Campbell, Mike; Partridge, Alison (My University, 2013)
Das Papier aus dem URBACT Arbeitskreis "More Jobs: Better Cities" bietet den Städten Handlungsmöglichkeiten an, die Arbeitsplätze schaffen können. Es richtet sich an Fachleute und politische Entscheidungsträger im kommunalen, nationalen und internationalen Umfeld, die sich mit der Erwerbstätigkeit in Kommunen beschäftigen.

This report from the URBACT Workstream "More Jobs: Better Cities" provides a framework for city action on jobs, which aims to help cities support and grow more and better jobs for the recovery. It is aimed at practitioners and policy-makers at the city level, as well as those at national and international levels, concerned with urban employment and skills policy and practice.
Keywords: Stadtentwicklung; Erwerbstätigkeit; Arbeit; Arbeitsmarkt; Beschäftigungsstruktur; Wirtschaftsstruktur; Beschäftigungsentwicklung